LABORATORY MARKERS OF LIVER DISEASES IN CHILDREN: FROM DIAGNOSIS TO TREATMENT MONITORING - Marufova Shaxzoda Furkatovna; Isomadinova Lola Kamolidinovna; Karimova Linara Alixanovna (Web of Journals Publishing, 2025)
Liver diseases in children can range from mild, self-limiting conditions to severe, life-threatening disorders. Early detection and accurate diagnosis are essential for effective management. Clinical laboratory diagnostics play a crucial role in identifying liver dysfunction and monitoring the progression of liver diseases. This article reviews common laboratory markers used in pediatric hepatology, including liver enzymes (ALT, AST), bilirubin, albumin, and prothrombin time, and their significance in diagnosing various hepatic conditions such as viral hepatitis, biliary atresia, and cirrhosis. The article also discusses the role of these markers in monitoring treatment response and disease progression.
Keywords: Liver diseases, pediatrics, laboratory diagnostics, ALT, AST, bilirubin, albumin, prothrombin time, hepatitis, biliary atresia, cirrhosis.